2004
DOI: 10.1523/jneurosci.3388-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitogen-Activated Protein Kinase Activation in Injured and Intact Primary Afferent Neurons for Mechanical and Heat Hypersensitivity after Spinal Nerve Ligation

Abstract: To investigate whether activation of mitogen-activated protein kinase (MAPK) in damaged and/or undamaged primary afferents participates in neuropathic pain after partial nerve injury, we examined the phosphorylation of extracellular signal-regulated protein kinase (ERK), p38 MAPK, and c-Jun N-terminal kinase (JNK) in the L4 and L5 dorsal root ganglion (DRG) in the L5 spinal nerve ligation (SNL) model. We first confirmed, using activating transcription factor 3 and neuropeptide Y immunoreactivity, that virtuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
209
4
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(242 citation statements)
references
References 93 publications
(92 reference statements)
26
209
4
3
Order By: Relevance
“…Specific antibodies against activated (phosphorylated) forms of MAPKs and specific inhibitors available for all three MAPK pathways have allowed us to study both the activation of MAPKs in the spinal cord and behavioral consequences of the activation. Inhibition of all three MAPK pathways at the spinal level have been shown to alleviate inflammatory pain and neuropathic pain (reviewed in ; also see Daulhac et al, 2006;Obata et al, 2004;Schafers et al, 2003;Zhao et al, 2007a). Interestingly, some glial inhibitors such as minocycline can inhibit the activation of MAPKs (Nikodemova et al, 2006).…”
Section: Map Kinase Activation In Microglia and Pain Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific antibodies against activated (phosphorylated) forms of MAPKs and specific inhibitors available for all three MAPK pathways have allowed us to study both the activation of MAPKs in the spinal cord and behavioral consequences of the activation. Inhibition of all three MAPK pathways at the spinal level have been shown to alleviate inflammatory pain and neuropathic pain (reviewed in ; also see Daulhac et al, 2006;Obata et al, 2004;Schafers et al, 2003;Zhao et al, 2007a). Interestingly, some glial inhibitors such as minocycline can inhibit the activation of MAPKs (Nikodemova et al, 2006).…”
Section: Map Kinase Activation In Microglia and Pain Controlmentioning
confidence: 99%
“…3e). Intrathecal MEK inhibitors were also shown to alleviate neuroapthic pain after spinal nerve ligation at time points when ERK is activated in spinal microglia (Obata et al, 2004;Zhuang et al, 2005). Thus, both ERK and p38 activation in spinal microglia are important for the pathogenesis of neuropathic pain.…”
Section: Map Kinase Activation In Microglia and Pain Controlmentioning
confidence: 99%
“…Recently MC4R was found in dorsal root ganglia (DRG) where nerve injury can affect its expression 3 , but the underlying mechanisms are still unclear. P38MAPK was improved to play an important role in the development and maintenance of nerve injury, inflammation and incision pain [4][5][6][7][8][9] . Intrathecal inhibitor of p38 has been shown to attenuate neuropathic pain in different ABSTRACT: Background: neuropathic pain is characterised by spontaneous ongoing or shooting pain and evoked amplified pain responses after noxious or non-noxious stimuli.…”
mentioning
confidence: 99%
“…Three distinct but interlinked MAP kinases have been identified in mammalian cells, including neurons (Sweatt, 2001;Obata et al, 2004), i.e, the extracellular-signal regulated kinase (ERK), the c-Jun -terminal kinase (JNK) and p38. Several lines of evidence have suggested that ERK cascades mediate cell development, growth and survival (Skaper and Walsch, 1998;Seger and Krebs, 1995), while p38 and JNK respond to inflammatory cytokines and cellular stress and promote inflammation and cell death (Schaeffer and Weber, 1999).…”
Section: Introductionmentioning
confidence: 99%